'A machine for recreating life': an introduction to reproduction on film. Issue 3 (19th September 2017) - OLSZYNKO-GRYN, JESSE; ELLIS, PATRICK
Abstract: Reproduction is one of the most persistently generative themes in the history of science and cinema. Cabbage fairies, clones and monstrous creations have fascinated filmmakers and audiences for more than a century. Today we have grown accustomed not only to the once controversial portrayals of sperm, eggs and embryos in biology and medicine, but also to the artificial wombs and dystopian futures of science fiction and fantasy. Yet, while scholars have examined key films and genres, especially in response to the recent cycle of Hollywood 'mom coms', the analytic potential of reproduction on film as a larger theme remains largely untapped. This introduction to a special issue aims to consolidate a disparate literature by exploring diverse strands of film studies that are rarely considered in the same frame. It traces the contours of a little-studied history, pauses to consider in greater detail a few particularly instructive examples, and underscores some promising lines of inquiry. Along the way, it introduces the six original articles that constitute Reproduction on Film .